NGHIÊN CỨU ỨNG DỤNG DUNG DỊCH HOẠT HÓA ĐIỆN HÓA ANOLIT ĐỂ KHỬ TRÙNG THÂN THỊT GÀ TRÊN DÂY CHUYỂN GIẾT MỔ CÔNG NGHIỆP - Châu, Nguyễn Hoài; Hà, Nguyễn Văn (Vietnam Journal of Science and Technology, 2012)
SUMMARY This study was undertaken to investigate the efficacy of anolyte mixed water (AMW) in killing pathogen bacteria on chicken carcasses under in laboratory testing and industrial processing conditions. In laboratory testing, chicken carcasses contaminated with bacteria solutions were subjected to treatment with anolyte (free chlorine 300 mg/l). The results indicated that Salmonella, S. aureus, Campylobacter reducing (1.38 log10 to 1.90 log10 cfu/g) were better than E.coli, C. perfringens and B. cereus reducing (0.43 log10 to 0.76 log10 cfu/g) after 30 s treatment. In industrial processing conditions, immersion treatments of chicken carcasses with AMW (free chlorine 50 mg/l) were significantly more effective than using water. The treatment of chickens carcasses by spraying AMW (free chlorine 50 mg/l) significantly reduced the bacteria population of E.coli and Coliforms by 2.19 log10 and 2.12 log10 cfu/cm2, respectively. The results also suggested that chicken carcasses may be prevented the cross-contamination in the chiller tank by using AMW (free chlorine 50 mg/l).